Office paper recyclability: first recycling - Benitez, Julieta Beatriz (2014)
Paper recyclability implies in the paper capacity to be recycled maintaining its properties to the maximum. Four commercial papers from Argentina and Brazil were studied, including three eucalyptus kraft (A, B, C) and one sugar cane bagasse soda-AQ (D), all with different bleaching processes. Their physical and chemical properties and a first laboratory recycling were evaluated. A refining of the pulp with a PFI mill, applying two energy levels at two different intensities - measured by number of revolutions and load - was accomplished to reach the same °SR (between 30 and 40, approximately). The refining energy and the yield were registered in each case. The properties of laboratory handsheets, and the aging to 24, 48, 72 and 144 hours were evaluated. The statistical analysis of the results indicates that the properties of the initial eucalyptus papers were similar, whereas they were generally inferior in the case of the bagasse paper. The bagasse and eucalyptus papers presented similar initial whiteness, but the first one had a higher reversion than the others. Once repulped, the eucalyptus papers A, B and C required, respectively, 4, 7 and 10 times greater energy than D, to obtain the same °SR. In all cases, the required energy to achieve the same °SR is slightly greater with the smaller refining intensity. The physical properties of the handsheets from the first recycle of paper D were, in general, lower. Among eucalyptus papers, B showed a slightly higher resistance and C, a slightly lower one. The mechanical properties of pulp sheets A, and D to a lesser extension, were more affected by the refining intensity than the rest, indicating a higher sensitivity of the fibers. The whiteness of the sheets of pulp B is lower than the rest. Opacity and light scattering coefficient of the sheets of pulp C were much higher than those of the other pulps.